Pt/POMs/TiO2 composite nanofibers with an enhanced visible-light photocatalytic performance for environmental remediation. Issue 35 (21st August 2019) - Shi, Hongfei; Zhao, Tingting; Zhang, Yue; Tan, Huaqiao; Shen, Wenhui; Wang, Weidong; Li, Yangguang; Wang, Enbo
Abstract : Pt/PMo12 /TiO2 composite nanofibers have been prepared and exhibit a highly efficient visible-light photocatalytic performance for removing methyl orange, tetracycline, Bisphenol A and Cr(vi ). Abstract : Herein, a novel series of PMo12 -TiO2 composites deposited with Pt nanoparticles (NPs), namely X %Pt/PMo12 /TiO2 (PMo12 = H3 PMo12 O40 ; X stands for wt% of Pt to the PMo12 /TiO2 sample and X = 3, 5, 8, and 10), were prepared through a simple electrospinning/calcination method, followed by photoreduction. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images showed that Pt NPs with an average size of 10 ± 5 nm are well dispersed on the PMo12 /TiO2 nanofibers. Photocatalytic tests revealed that the as-prepared Pt/PMo12 /TiO2 composite catalysts exhibited excellent and persistent photocatalytic activity for removing methyl orange, tetracycline, Bisphenol A and Cr(vi ) under visible-light illumination ( λ > 420 nm). Among the as-prepared composites, the 8%Pt/PMo12 /TiO2 sample displayed the best photocatalytic activity with the rate constants of 0.011 min −1 (MO), 0.043 min −1 (TC), 0.00615 min −1 (Bisphenol A) and 0.053 min −1 (Cr(vi )). The addition of POM PMo12 to the composites enhanced the visible-light adsorption and redox ability of TiO2 . Furthermore, Pt NPs exhibited localized surface plasmon resonance (LSPR) absorption, therefore improving the absorption of visible light by PMo12 /TiO2 . Additionally, intense local electromagnetic fields resulted from LSPR, which greatly facilitated the separation of photo-produced charge carriers in Pt/PMo12 /TiO2 . The results of free radical- and hole-trapping tests suggested that ˙OH and ˙O2 − were responsible for the degradation of MO/TC. Finally, the corresponding photocatalytic mechanism was proposed.